The Golden CAPM - Hasler, Michael Nicolas; Stici, Constantin (Elsevier BV, 2025)
When asset returns are measured in ounces of gold rather than U.S. dollars, the Capital Asset Pricing Model (CAPM) holds. Indeed, regressing asset returns onto market betas yields an intercept that is economically small and statistically indistinguishable from zero. Moreover, the slope is remarkably close to the average market return and statistically significant. That is, the golden CAPM successfully explains the cross-section of expected returns. We show that denominating returns in ounces of gold improves the explanatory power of multi-factor models such as the Fama-French 3-, 5-, and 6-factor models, and the Carhart 4-factor model. Yet, across all model-test asset combinations, none outperforms the simple golden CAPM applied to beta-sorted portfolios.
Keywords: Capital Asset Pricing Model; Asset Pricing Tests; Gold